Acromegaly without acral anomalies - Mara Carsote; Florica Sandru; Diana Elena Rentea; Claudia Mehedintu; Stefania Zugravu; Corina Chirita; Mihai Cristian Dumitrascu (Romanian Journal of Medical Practice, 2021)
Early recognition of a pituitary secretor tumor offers a better prognostic; thus acromegaly might be recognized before the actual clinical picture of acromegaly is detectable. This is a 59-year old, non-smoking female admitted for: post-operatory evaluation of acromegaly. The clinical evaluation is non-specific. One year prior she was diagnosed with acromegaly based on cerebral imaging assessment due to intermittent headache. She was treated with cabergoline a few months before neurosurgery was done; post-operatory panel showed complete remission of acromegaly. Prompt detection of the disease allowed the early intervention with a very good outcome. The remission of GH excess after neurosurgery depends on tumor size and practical experience of the surgeon. The longer time of high growth hormone levels exposure the higher is the risk of cardio-metabolic and oncologic complications.